A New Approach for Synthesizing the Hybrid Silica Aerogels. (2015) - Mazraeh-shahi, Z. Talebi; Shoushtari, A. Mousavi; Bahramian, A.R.
Abstract: Uniform Polyurethane/silica hybrid aerogels were achieved at ambient pressure via an approach in which an aqueous polyurethane dispersion was used and the hybridization step carried out before gelation step. The FT-IR spectra confirmed the incorporation of polymer chains into the silica network and hybrid network formation. As the H2 O/TEOS molar ratio increased after hybridization in this method, the effect of H2 O/TEOS molar ratio changes and PU content on the density of hybrid aerogels was investigated separately. The density of native silica aerogels decreases commonly with increasing the water content while increasing the aqueous PU dispersion content increases the density of hybrid aerogels. The density difference between the hybrid aerogel sample with a certain aqueous PU dispersion and the similar native silica aerogel with the same H2 O/TEOS molar ratio demonstrated the intensive polyurethane chain effect on the aerogel density. The results showed that the simultaneous increase of H2 O/TEOS molar ratio and PU content could be led to the uniform structure of hybrid aerogels. However, the effect of polyurethane on the aerogel density was more sensitive than H2 O/TEOS molar ratio effect especially in high polyurethane content (≥10 wt.%) that increased the density of hybrid aerogels.